John Henry Newman on emotions in parochial sermons - Primc, Liza (Bogoslovni vestnik, 2025)
The presented article1 examines John Henry Newman’s theology of emotions through an analysis of selected Parochial Sermons. It argues that Newman understands emotions as mediators between doctrinal truth and the lived reality of faith embodied in the Church. His understanding of emotions is rooted in personal experience: from youthful evangelical fervour, through disappointment at the liberalisation of parliament and the established Church, to a commitment to living according to the teachings of Christ. Newman identifies three key ideas: (a) emotions are legitimate but require constant formation; (b) worship and communal prayer do not suppress emotions but guide them towards calmness; (c) the source and direction of religious emotions is conscience, which leads a person to God. For Newman, emotions are consecrated in Christ and sustained in the Church, where they become expressions of compassion, community, and God’s love. The article concludes by demonstrating how Newman’s integration of reason and emotion offers a Christian approach to emotions that remains relevant to contemporary theological discourse.
Keywords: Anglican period; anglikansko obdobje; čustva; ecclesiology; ekleziologija; emotions; Newman, John Henry; Parochial Sermons; pridige; sermons; teologija čustev; theology of emotion; Victorian era; viktorijanska doba; Župnijske pridege